Design and Development of PM Application based on IoT Technology - NUR HIDAYAH BINTI ZAINI; HANAYANTI BINTI HAFIT (Applied Information Technology And Computer Science, 2024)
The Internet of Things (IoT) technology has widespread applications in sectors like agriculture, healthcare, business, and finance. This project focuses on using Microbit as a soil moisture sensor in agriculture. It connects to ThingSpeak and a mobile application that sends reminders to users for timely watering. The project aims to address the challenge of forgetting to water plants due to busy lifestyles, benefiting plant health. Objectives include designing the Microbit sensor, developing a monitoring app with reminder functionality, and conducting thorough testing. The project primarily supports farmers in dry regions of Perlis, Malaysia, aiming to enhance agricultural practices and manage plant moisture levels effectively for optimal growth. Based on testing with users, the application's user interface received positive feedback. Most features worked well, the reminder feature could be improved for timely notifications. Initially, setting up ThingSpeak and Microbit may require some time and understanding, but it becomes easier with experience.